Unveiling unique allergenic properties of rapeseed oil: A clinical case study - Margarida Gomes, MD; Maria José Martinez, MSC; Fernando Pineda, PhD; Ana Mendes, MD (Journal of Allergy and Clinical Immunology: Global)
Rapeseed oil (Brassica napus), a plant from the Brassicaceae family, is widely utilized in culinary practices and industrial applications. Despite the prevalence of rapeseed oil, its allergenic potential remains largely unexplored, particularly in the context of food allergies. This study investigates a potential food allergy linked to rapeseed oil.